The Effectiveness of Local Wisdom-Based Storytelling Marketing and Perceived Value on Purchase Decisions for Lunggi Sambas Woven Fabric Mediated by Trust - Tsabitah, Dhiyaa Ayu; Dewi Rawa, Ricola; Ariffin, Muchammad (JURNAL MANAJEMEN MOTIVASI, 2026)
This study investigates the influence of local wisdom-based storytelling marketing and perceived value on purchase decisions for Sambas Lunggi woven fabric, with consumer trust as a mediating variable. Using a quantitative approach, data were collected from 160 consumers and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that storytelling marketing and perceived value significantly enhance consumer trust. Perceived value and trust positively affect purchase decisions, whereas storytelling marketing has no significant direct effect. Trust mediates the relationships between storytelling marketing, perceived value, and purchase decisions. These findings highlight the importance of trust in strengthening the competitiveness of local cultural products.